Emeia gen. nov., a new genus of Luciolinae fireflies from China (Coleoptera: Lampyridae) with an unusual trilobite-like larva, and a redescription of the genus Curtos Motschulsky - Fu, Xinhua; Ballantyne, Lesley; Lambkin, Christine (Zootaxa, 2012)
Emeia, a new genus of Luciolinae fireflies, is described from males, flightless females and unusual trilobite-like larvaefor a single species pseudosauteri (Geisthardt) transferred from Curtos Motschulsky. Flashing patterns and ecological dataare presented. A phylogenetic analysis covering 143 Luciolinae species uses 436 morphological characters of males, fe-males and larvae to support the erection of the new genus. A generic redescription of Curtos Motschulsky from a restricted number of species is given. A key to genera and certain species groups using males is provided.